Pengembangan video pembelajaran matematika untuk melatih kemampuan analisis siswa SMA pada materi dimensi tiga - Afni, Sanika Nur; Ningsih, Yunika Lestaria; Octaria, Dina (Karoteh Utama, 2023)
This study aims to develop mathematics learning videos to train students' analytical skills in three-dimensional materials that are valid, practical, and have potential effects. The development of these learning videos employs the ADDIE research method, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Research data were obtained through validation questionnaires, student response questionnaires, and student learning outcome tests. The trial subjects were 12th-grade science students at SMA Negeri 7 Palembang, South Sumatra. Based on the analysis of data obtained from expert validation, the mathematics learning videos to train students' analytical skills in three-dimensional materials were deemed